An Analysis of Errors in the Use of Formal Language in Narrative Writing of Students at SMP Negeri 1 Samudera - Ulfia; Azhari; Muntazar; Ririn Rahayu; Rani Ardesi Pratiwi; Maulidawati (Indonesian Journal of Education and Social Humanities, 2025)
This study is entitled “The Use of Formal Language Variety in Narrative Writing of Students at SMP Negeri 1 Samudera” and was conducted in the even semester of the 2024/2025 academic year. The study aims to identify errors in the use of formal language variety in narrative texts written by eighth-grade students during the even semester of the 2024/2025 academic year. The research was carried out at SMP Negeri 1 Samudera in April 2025. A qualitative descriptive method was employed in this study. The data source consisted of narrative texts written by eighth-grade students of SMP Negeri 1 Samudera in the 2024/2025 academic year. The most common errors found in students’ narrative writing were the use of informal words resulting from spelling deviations, particularly in the use of the preposition di-. These errors were predominantly committed by students of class 8.3. Students in class 8.4 also made similar errors, mainly due to the use of non-standard spellings. These mistakes occurred because students paid insufficient attention to, and in some cases underestimated, formal writing conventions. Informality caused by vowel and consonant omission or substitution occurred less frequently; however, errors involving consonant substitution were highly prevalent, especially in the word “poto” instead of “foto.” This phenomenon is attributed to students’ habitual pronunciation of “foto” as “poto,” which subsequently influenced their written production. The factors contributing to informal language use in students’ narrative writing include: (1) vowel substitution, (2) vowel omission, (3) consonant substitution, (4) consonant omission, and (5) spelling-related distinctions.